Pengaplikasian Pupuk Kasgot dan Air Cucian Ikan untuk Produksi Mikrogreen Pakcoy: Application of Kasgot Fertilizer and Fish Washing-Water for PakChoi Microgreens Production - Farhanah A; Faisal Hamzah; Atika; Taufik Hidayat; Jabal R Ashar (Jurnal Agroekoteknologi dan Agribisnis, 2023)
Kasgot fertilizer is one of the potentials that the community can utilize to become organic fertilizer. On the other hand, milkfish is one of the strategic commodities to fulfill protein that is favored by the people of Indonesia, especially Makassar. However, milkfish washing water waste is usually thrown away, causing environmental pollution. This study aims to determine the effectiveness of the fulfillment of nutrients in mustard microgreens through the application of cassava fertilizer and milkfish washing water and to determine the level of knowledge, attitudes, and skills of farmers towards the fulfillment of nutrients in mustard microgreens through the provision of cassava fertilizer and milkfish washing water. This study method used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatments and 4 replications. The first factor consists of K0 = soil (100%), K1 = kasgot 10%, K2 = kasgot 30%, K3 = kasgot 50%. The second factor consisted of B0 = Control, B1 = milkfish washing water 50 mL/L, B2 = milkfish washing water 100 mL/L. Application of 10% kasgot fertilizer was effective on plant fresh weight with a value of 0,926 g, adding root volume to 0,80 mL, chlorophyll with a value of 6,342 and leaf area with a value of 11,72 cm2. The results of this study concluded that the application of kasgot fertilizer by 10% had a real effect on increasing the production of pakchoi microgreens.